From Feline Idiopathic Ulcerative Dermatitis to Feline Behavioral Ulcerative Dermatitis: Grooming Repetitive Behaviors Indicators of Poor Welfare in Cats - Titeux, Emmanuelle; Gilbert, Caroline; Briand, Amaury; Cochet-Faivre, Noëlle (Frontiers in Veterinary Science, 2018)
Feline idiopathic head-and-neck dermatitis - also named feline idiopathic ulcerative dermatitis (IUD) - is considered as a rare skin disease of unknown origin. It is usually associated with a crusted, non-healing, self-induced ulcer occurring most commonly on the dorsal or lateral neck or between the scapula where self-grooming by scratching occurs. Usually, IUD is diagnosed after exclusion of other causes of pruritus. In feline medicine, self-induced alopecia is recognized as a behavioural disorder (abnormal repetitive behaviour) due to excessive licking which is an amplification of a normal maintenance behaviour. Such repetitive behaviours, like self-induced alopecia or self-induced wounds, are named stereotypies and considered as indicators of poor welfare. The objectives of our study were to determine, firstly, if the repetitive behavior associated with self-induced wounds was related to a poor welfare, and, secondly, if improving the welfare in the cat’s environment would lead to healing thanks to environmental enrichment. We recruited 13 cats diagnosed with IUD by a dermatologist. These cats were referred to a behaviorist for welfare evaluation. A welfare score was attributed using a newly-developed 21-point welfare scale. The median score of the 13 IUD cats was 16, while the median score of 35 healthy cats was 7 (significant difference, p<0,001). Major modifications of the cat’s environment and the human-cat relationship were then recommended for IUD cats. Within 15 days after environment modifications, ulcerative lesions were healed and welfare scores improved significantly (median score of 6, significantly different from the score before environmental modifications), being similar to healthy cats (no significant differences). Only one cat was treated with a psychotropic drug, owners being reluctant to improve environmental modifications. These results suggest that feline IUD is a behavioural disorder indicative of poor welfare and that it requires management by behaviour specialists, proposing environmental modifications. We hence propose to rename this affection to “behavioural self-induced ulcerative dermatitis”, given that welfare scores were significantly different from healthy cats, and that environmental modifications modified welfare scores and lead to successful healing in all cases.